QUALITY OF WORK LIFE THE POWER OF INSURANCE COMPANY: IMPACT OF PERSONAL FACTORS ON THE QUALITY OF WORK LIFE OF THE OFFICER - G. BALACHANDAR; N. PANCHANATHAM; K. SUBRAMANIAN (Management & Marketing)
Quality of work life is the beautiful experience which an employee feels about the job and work place. It gives benefit to the organisation as well as to the employees. This research paper studies the impact of personal factors of insurance company officers on the quality of work life. The total size of the sample is 340. To collect data, life insurance and general insurance company officers were considered for the study. Interview schedule method was administered to gather information. The collected data were processed and then analysed with the help of descriptive statistics method, t-test, and ANOVA method. The result of the study is discussed in the research paper.